Assessing national-level provision of conservation capacity building: lessons learnt from a case study of Kenya. Issue 5 (29th September 2022) - O'Connell, Mark; Donnison, Amy; Lynch, Kenny; Bennett, Rachel
Abstract: As global environmental pressures grow, the need for delivering relevant and sustainable capacity building in conservation has never been greater. Individuals, organizations and communities need the skills, knowledge and information that allow them to address environmental issues at a variety of spatial scales and in diverse contexts. Capacity is currently built through a range of activities, including tertiary education, training courses, online learning, mentoring and continuing professional development. However, a significant proportion of the current capacity-building provision is non-strategic, project-based and reactive. The conservation sector still lacks a coordinated approach to capacity building linked to broader conservation goals. Without an assessment of current capacity-building provision and future capacity needs, the delivery of capacity building in conservation will remain fundamentally ad hoc. The need for strategic conservation capacity building in sub-Saharan Africa has been identified and here we report on the first collation of online material to assess current conservation capacity provision in Kenya (the country with the greatest online capacity-building presence). We reviewed a total of 177 capacity-building initiatives delivered during 2014–2019 and recorded 55 separate metrics for each initiative. We present: (1) a broad overview of the data collation methods developed, (2) examples of data that will support strategic capacity-building strategies, and (3) the lessons learnt from this assessment.